BLOCKCHAIN SECURITY OF AUTONOMOUS MARITIME TRANSPORT - Petković, Miro; Mihanović, Vice; Vujović, Igor (Journal of Applied Engineering Science, 2019)
Autonomous ships are in experimental stage nowadays with Maritime Autonomous Surface Ships (MASS) already defined by IMO. Since MASS rely heavily on communications, security of communication systems and data security is critical. Secure communication is required to avoid bad actors to interfere with the communications or seizing control of a autonomous ship. In this paper, implementation of blockchain technology to improve autonomous vessels control security is investigated. This technology is already used in maritime bill of lading, acts on ship’s technical inspection and for more accurate container tracking etc. The paper is organized as follows: first section describes current status on autonomous ships, basic definitions and terms, second section describes what is blockchain technology and how does it work, third section deals with blockchain technology applications with the proposed usage of the technology in autonomous vessels control scheme.